Analisis Perbandingan Metode SAW dan TOPSIS dalam Sistem Pendukung Keputusan Seleksi Calon Dosen STMIK Palangkaraya - Hendartie, Susi (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2017)
The concept of decision-making aids program is currently growing very rapidly. There are so many methods that used to assist in the decision-making process. There are two methods that can be used to solve the problem of Multi-Attribute Decision Making (MADM); TOPSIS and SAW method. This is because those methods are simple, easy to understand, computing efficient and has the ability to measure the relative performance of decision alternatives in a simple mathematical form. The problem of this study is to solve a particular MADM case which it may be difficult to determine which method is the most relevant between the SAW and TOPSIS methods. Therefore a sensitivity test was conducted to determine the most appropriate method between SAW and TOPSIS in the settlement of the case. In this problem solving the problem of Multi-Attribute Decision Making (MADM) had done through Sensitivity Test process first, then by using the method between SAW or TOPSIS is aimed to assist everyone in decision-making based on best alternative value